Impact of Organization and Administration of Motor Vehicle Mechanics Work Workshop for Improving Skill Acquisition - Kumazhege, Stephen Z.; Babaji, Ibrahim (Engineering Science Letter, 2024)
The study aims to investigate the organization and administration of the Motor Vehicle Mechanics Work (MVMW) Workshop in Government Science and Technical Colleges in Gombe State, Nigeria, focusing on improving student skill acquisition. The study, which had two research questions and hypotheses, adopted a descriptive survey research design, and the study population comprised 42 administrators (principals, vice principals, senior masters and mistresses, and MVMW Head of Departments) and 21 MVMW teachers, making a total of 63 respondents. Whole population sampling was adopted for the study. A researcher-developed questionnaire collects data, with responses rated on a Likert scale. Descriptive statistics, such as mean and standard deviation, were employed to answer research questions, and a t-test was used to test hypotheses. The findings reveal that the organizational and administrative structures significantly impact skill acquisition in the MVMW Workshop. Administrators and teachers agree on the positive effects of these structures. Recommendations are proposed, emphasizing the need for well-designed organizational layouts, effective administrative systems, and collaborative efforts between administrators and teachers to optimize workshop functionality and enhance student skill development.